Experimental warming shows that decomposition temperature sensitivity increases with soil organic matter recalcitrance - Haddix, Michelle L., author; Conant, Richard T., author; Steinweg, J. Megan, author; Six, Johan, author; Paul, Eldor A., author; Plante, Alain F., author; Ecological Society of America, publisher (Colorado State University. Libraries, 2008)
Soil C decomposition is sensitive to changes in temperature, and even small increases in temperature may prompt large releases of C from soils. But much of what we know about soil C responses to global change is based on short-term incubation data and model output that implicitly assumes soil C pools are composed of organic matter fractions with uniform temperature sensitivities. In contrast, kinetic theory based on chemical reactions suggests that older, more-resistant C fractions may be more temperature sensitive. Recent research on the subject is inconclusive, indicating that the temperature sensitivity of labile soil organic matter (OM) decomposition could either be greater than, less than, or equivalent to that of resistant soil OM. We incubated soils at constant temperature to deplete them of labile soil OM and then successively assessed the CO2-C efflux in response to warming. We found that the decomposition response to experimental warming early during soil incubation (when more labile C remained) was less than that later when labile C was depleted. These results suggest that the temperature sensitivity of resistant soil OM pools is greater than that for labile soil OM and that global change-driven soil C losses may be greater than previously estimated.
Keywords: decomposition; soil organic matter; temperature sensitivity